Influence of preparation design, restorative material and load direction on the stress distribution of ceramic veneer in upper central incisor - Meirelles, Laura Célia Fernandes [UNESP]; Pierre, Fernanda Zapater [UNESP]; Tribst, João Paulo Mendes; Pagani, Clovis [UNESP]; Bresciani, Eduardo [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Editora Cubo, 2021)
Objective: Evaluate the effect of four preparation designs, two ceramic materials, and two occlusion contact types on the stress distribution of ceramic veneer in upper central incisor. Material and methods: 3D-models were performed in the modeling software containing enamel, dentin, pulp, periodontal ligament and a base of polyurethane resin. The designs were modeled and exported to the computer aided engineering software to perform the static structural analysis. For the mesh, a total of 155429 tetrahedron elements and 271683 nodes were used, after a 10% convergence test. Two materials, lithium disilicate and feldspathic ceramics, were simulated. A static load of 100 N on 45º was applied on the incisal and middle thirds of the palatal tooth region, guided by the occlusal plane. The base was constrained in all directions. The Maximum Principal Stress was the failure criteria chosen for the analysis. Results: The Finite Element Analysis showed that the most conservative designs presented less stress concentration on the ceramic veneer. However, the highest tensile stress concentrations were observed on lithium disilicate veneer with extend design, on the middle third. The type of occlusal contact presented different stress patterns among the preparation designs; the incisal contact showed higher stress concentration compared to middle third contact regardless the ceramic material. Conclusion: To perform a ceramic veneer in upper central incisor, the feldspathic ceramic presented promising results and should be recommended when the extended design was done. Regarding contact types, the incisal contact is more prone to failure regardless the ceramic and preparation design.
Influência do desenho de preparo, material restaurador e direção de carga na distribuição de tensão de laminado cerâmico em incisivo central superior
Keywords: Ceramics; Dental veneers; Finite element analysis